Mansonella ozzardi mitogenome and pseudogene characterisation provides new perspectives on filarial parasite systematics and CO-1 barcoding - Crainey, James Lee; Marín, Michel Abanto; Silva, Túllio Romão Ribeiro da; de Medeiros, Jansen Fernandes; Pessoa, Felipe Arley Costa; Santos, Yago Vinícius; Vicente, Ana Carolina Paulo; Luz, Sérgio Luiz Bessa (Scientific reports, 2018)
Despite the broad distribution of M. ozzardi in Latin America and the Caribbean, there is still very little DNA sequence data available to study this neglected parasite’s epidemiology. Mitochondrial DNA (mtDNA) sequences, especially the cytochrome oxidase (CO1) gene’s barcoding region, have been targeted successfully for filarial diagnostics and for epidemiological, ecological and evolutionary studies. MtDNA-based studies can, however, be compromised by unrecognised mitochondrial pseudogenes, such as Numts. Here, we have used shot-gun Illumina-HiSeq sequencing to recover the first complete Mansonella genus mitogenome and to identify several mitochondrial-origin pseudogenes. Mitogenome phylogenetic analysis placed M. ozzardi in the Onchocercidae “ONC5” clade and suggested that Mansonella parasites are more closely related to Wuchereria and Brugia genera parasites than they are to Loa genus parasites. DNA sequence alignments, BLAST searches and conceptual translations have been used to compliment phylogenetic analysis showing that M. ozzardi from the Amazon and Caribbean regions are near-identical and that previously reported Peruvian M. ozzardi CO1 reference sequences are probably of pseudogene origin. In addition to adding a much-needed resource to the Mansonella genus’s molecular tool-kit and providing evidence that some M. ozzardi CO1 sequence deposits are pseudogenes, our results suggest that all Neotropical M. ozzardi parasites are closely related.